Evaluation of Handheld Assays for the Detection of Ricin and Staphylococcal Enterotoxin B in Disinfected Waters - Mary Margaret Wade; Tracey D. Biggs; Joseph M. Insalaco; Lisa K. Neuendorff; Vicky L. H. Bevilacqua; Amanda M. Schenning; Lisa M. Reilly; Saumil S. Shah; Edward K. Conley; Peter A. Emanuel; Alan W. Zulich (International Journal of Microbiology)
Development of a rapid field test is needed capable of determining if field supplies of water are safe to drink by the warfighter during a military operation. The present study sought to assess the effectiveness of handheld assays (HHAs) in detecting ricin and Staphylococcal Enterotoxin B (SEB) in water. Performance of HHAs was evaluated in formulated tap water with and without chlorine, reverse osmosis water (RO) with chlorine, and RO with bromine. Each matrix was prepared, spiked with ricin or SEB at multiple concentrations, and then loaded onto HHAs. HHAs were allowed to develop and then read visually. Limits of detection (LOD) were determined for all HHAs in each water type. Both ricin and SEB were detected by HHAs in formulated tap water at or below the suggested health effect levels of 455 ng/mL and 4.55 ng/mL, respectively. However, in brominated or chlorinated waters, LODs for SEB increased to approximately 2,500 ng/mL. LODs for ricin increased in chlorinated water, but still remained below the suggested health effect level. In brominated water, the LOD for ricin increased to approximately 2,500 ng/mL. In conclusion, the HHAs tested were less effective at detecting ricin and SEB in disinfected water, as currently configured.